THE ROLE OF BROCA’S AREA IN SYNTAX: A TMS STUDY ON WRITTEN GREEK LANGUAGE - Maria-Korina, Stefopoulou; Elizabeth, Chroni; Anastasios, Bezerianos; Elias D., Kouvelas; Arhonto, Terzi; Adamantia, Mitsacos (European Scientific Journal, ESJ, 2015)
A number of recent papers have addressed the potential of transcranial magnetic stimulation (TMS) to interfere with linguistic processes or speech production. In this paper we present an experiment with TMS to clarify the role of Broca’s area in syntactic processing. An experimental paradigm contrasted sentences that require syntactic and semantic decisions on written Greek language. We found a clue of selective priming effects on syntactic decisions but not on semantic decisions. Our results provide evidence of the involvement of Broca’s area in syntax.